Genetic architecture, inter-relationship and selection indices in F4 generation of barley (Hordeum vnlgare) - YADAV, SUNIL KUMAR; SINGH, SMITA; PANDEY, PRAVEEN; BAGHEL, SATISH SINGH; SINGH, ASHOK KUMAR (The Indian Journal of Agricultural Sciences, 2015)
The experimental material consisting of 24 F4 segregating populations obtained by crossing of 32 parents of barley (Hordeum vulgare L.) were grown in randomized block design with four replications during rabi 2013–14 at JNKVV, Instructional farm, College of Agriculture, Rewa (MP). Thirty randomly competitive plants were selected to record the observation on days to 50% heading, days to maturity, plant height, number of tillers/plant, spike length, grains/ spike, 1 000 grain weight, biological yield/plant, harvest index and grain yield/plant. Significant differences were found for all the traits. The genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) were high for grain yield/plant and tillers/plant. High heritability coupled with high genetic advance as percent of mean was registered for grains /spike, biological yield/plant, 1 000 grain weight and grain yield/plant indicated predominance of additive gene action. Significant and positive association exhibited by grain yield/plant with spike length, grains/spike, biological yield/plant and 1 000 grain weight. Based on linear combination of traits, sequential and simultaneous selection indices revealed that out of 24 genotypes, 14 genotypes were sorted for higher yield and its components. Crosses, viz. K 792 × BH 674, JB 284 × PL 751, JB 1 × NDB 1276, K 792 × NDB 1276, RD 2668 × K 792, RD 2581 × JB 1 and RD 2503 × JB 58 were identified as superior genotypes having high genetic potential for grain yield.